Archaeology of Cross-Cultural Interactions at Amedeka, Akuse, Eastern Region, Ghana - Darko-Yeboah, B. (University Of Ghana, 2016)
This study investigates the nature of interactions that existed at Amedeka and Akuse between Africans and Europeans. The objective of the study was to generate information on the legacy of multinational economic interactions at Amedeka and to derive additional archaeological data to facilitate reconstruction of past socio-economic and cultural life-ways in the area. It also sought to document factors which facilitated the growth of commercial network, identify the major local agents involved in trade and the reasons or factors that led to the collapse of commercial activity in the area in the early 20th century. The artefacts recovered helped establish a chronology of the site of Akuse-Amedeka. A multidisciplinary approach involving gathering of oral account, documentary and archival records, ethnographic and archaeological data were adopted in this study. The result revealed various levels of interactions (economic, social, political and cultural) between the local people and their European counterparts. The main reason for this interaction was the location of the research area which prevented Europeans from travelling up north to trade as a result of the presence of huge boulders of rocks in that part of the Volta River. This led to the establishment of multinational companies which attracted other local people from neighboring towns to the area, thus the multi-ethnic nature of the area. This research therefore gives an insight into an inland interaction at a 19th century port created at Amedeka leading to trade in various goods, including palm oil and cocoa which were exported in exchange for European materials. The study will therefore serve as a contribution to the study of inland trading activities and interactions in Ghana.
Thesis (MPhil.)
Keywords: Cross-Cultural Interactions; Archaeology; Cultural Life-Ways; Ghana